Laboratory study on magnetization reduction of CO - Li Y.; Yuan S.; Han Y.; Zhang S.; Gao P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, magnetizing roasting in fluidized bed was employed to separate iron minerals from red mud. The effect of treatment conditions on product quality was investigated. In addition, the phase transformation, changes in magnetism, and microstructures were studied by thermodynamic analysis, chemical analysis, X-ray diffraction technique (XRD), vibrating sample magnetometer (VSM), and optical microscopy. The magnetic concentrates with the total iron grade of 57.65% and recovery of 90.04% were obtained under the optimum conditions. XRD and chemical analysis demonstrated that 92% iron minerals in red mud converted to magnetite. VSM further confirmed that the magnetism of roasting products was strongly enhanced, and the specific susceptibility increased from 1.9Ч10-5 m3/kg to 2.9Ч10-4 m3/kg after magnetizing roasting. Hence, fluidized magnetizing roasting is an effective technology for recovering iron minerals from high-iron red mud.